Multicolor x-rays from free electron-driven van der Waals heterostructures - Huang, Sunchao (2023)
The emergence of van der Waals (vdW) heterostructures has led to precise and versatile methods of fabricating devices with atomic-scale accuracies. Hence, vdW heterostructures have shown much promise for technologies including photodetectors, photocatalysis, photovoltaic devices, ultrafast photonic devices, and field-effect transistors. These applications, however, remain confined to optical and suboptical regimes. Here, we theoretically show and experimentally demonstrate the use of vdW heterostructures as platforms for multicolor x-ray generation. By driving the vdW heterostructures with free electrons in a table-top setup, we generate x-ray photons whose output spectral profile can be user-customized via the heterostructure design and even controlled in real time. We show that the multicolor photon energies and their corresponding intensities can be tailored by varying the electron energy, the electron beam position, as well as the geometry and composition of the vdW heterostructure. Our results reveal the promise of vdW heterostructures in realizing highly versatile x-ray sources for emerging applications in advanced x-ray imaging and spectroscopy.